2018
DOI: 10.1007/s10096-018-3332-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of intravenous acyclovir-induced nephrotoxicity

Abstract: To assess the incidence, predictive factors, and prognosis of acyclovir-induced nephrotoxicity. We conducted a historical prospective cohort study of patients treated with intravenous acyclovir in North Denmark Region from 2009 to 2016. Information on baseline demographics, co-morbidities, plasma creatinine, and treatment was obtained from the medical records. The primary outcome was an increase of ≥ 40 μmol/L in plasma creatinine level from baseline. We included 276 patients treated with intravenous acyclovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Literature review found that a delay in recognition and treatment may result in severe morbidity: Nephrotoxicity developed in only 5% to 10% of the cases in a prospective cohort of 276 patients. 13 In conclusion, HSE may develop following neurosurgical resection and the threshold for suspicion of HSE should be extremely low in a patient who shows compatible symptoms (encephalopathy, fever, and seizures) or does not recover as planned. Moreover, in case of suspicion of HSE, acyclovir should be promptly started until infection can be definitely ruled out.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Literature review found that a delay in recognition and treatment may result in severe morbidity: Nephrotoxicity developed in only 5% to 10% of the cases in a prospective cohort of 276 patients. 13 In conclusion, HSE may develop following neurosurgical resection and the threshold for suspicion of HSE should be extremely low in a patient who shows compatible symptoms (encephalopathy, fever, and seizures) or does not recover as planned. Moreover, in case of suspicion of HSE, acyclovir should be promptly started until infection can be definitely ruled out.…”
Section: Discussionmentioning
confidence: 97%
“…There have been case reports of acute kidney injury precipitated by acyclovir, 11,12 though a prospective cohort study of 276 patients showed acyclovir-induced nephrotoxicity in only 5% to 10% of cases, all of which were reversible with IV hydration, dose reduction, or discontinuation of the drug. 13 The use of antivirals may reduce morbidity and mortality of HSE, whether it occurs by latent reactivation or primary infection 3 ; and given the life-threatening nature of HSE, the benefits of treatment may outweigh the risk of untreated disease or potential nephrotoxicity of acyclovir, which could be avoided by adequate hydration and renally adjusting the dose.…”
mentioning
confidence: 99%
“…Acyclovir is a nephrotoxic drug often implicated in ARF [6,7] by a mechanism of precipitation (crystals) and acute tubular necrosis. Reports of ARF are frequent [8][9][10][11][12][13] and are accompanied by classical risk factors: high dose administration, water-soluble depletion and combination with other nephrotoxic drugs, leading to a recommendation for slow infusion administration with hydration. In patients with renal insufficiency, dosage reduction is required.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published trial, IV acyclovir treatment at 5 mg/kg TID was considered safe, with no difference in renal failure, creatinine increase, and renal replacement therapy rates compared to the placebo group [6]. Richelsen et al described nephrotoxicity in 5.1-10.5% of patients receiving 10 mg/kg acyclovir TID, which was fully reversible [7]. Moreover, older studies already showed that nephrotoxicity was usually reversible and could be minimised by slow infusion and adequate hydration [8].…”
Section: Authors' Responsementioning
confidence: 99%